Porous three-dimensional activated microwave exfoliated graphite oxide as an anode material for lithium ion batteries. Issue 60 (8th June 2016) - Zhu, Xianjun; Zuo, Linwen; Wu, Shuilin; Qu, Xiaodi; Wei, Meng; He, Li; Zhong, Yu; Zhu, Yanwu
Abstract : 3D porous aMEGO has been achieved with high SSA and improved electrochemical performance for LIBs. Abstract : A porous graphene nanosheet, with a Brunauer–Emmett–Teller surface area of up to ∼3100 m 2 g −1, is prepared by using chemical activation of microwave exfoliated graphite oxide. The sp 2 -bonded carbon has a continuous three-dimensional network of highly curved atom-thick walls with ∼1 to 5 nm width pores. As an anode material for lithium ion batteries, it can deliver a reversible specific capacity of ~1600 mA h g −1 at the current of 100 mA g −1 . To understand the Li storage mechanism, porous carbon samples with tunable specific surface area were investigated. The high reversible capacity indicates that the meso- and micropores are the key factor for Li insertion/extraction during discharging and charging. The porous structure and large specific surface area is believed to have contributed to the high performance.